Students and Teachers Attitudes on Using Smart Board Technology in Different Classes - Al-Zayed, Dr. Norma (Opción, 1970)
Individuals´ attitudes with technology present (show) index of the materials consumed. During most of the twenty-first century, technology has enhanced enormously. Students’ and their teachers’ attitudes are fatal in the operative and dynamic use of technology. This current study’s purpose was to resolve the attitudes of students’ and their teachers’ while using technology in classrooms. The study group contains students from grades 6 to 8 and their teachers. This adjectival study is a quantitative research method (Karasar, 2005). The data obtained were evaluated by using a 3-point Likert type questionnaire prepared by the researcher. Frequencies and percentages were used in the analyses.